A Proposed Training Program Using Cross – Training On The Development of Some Physical Traits In College of Physical Education And Sport Sciences Students - Adnan, Othman; Hassan, Abdullah (Journal of Physical Education, 2018)
A Proposed Training Program Using Cross – Training On The Development of Some Physical Traits In College of Physical Education And Sport Sciences StudentsThe research aimed at identifying the effect of cross training on senior college students/ university of Mosel as well as designing cross – training exercises to identify their effect on special physical traits in senior college of physical education students. The subject were (128) forth year college of physical education and sport sciences/ university of Mosel (2017 – 2018). The researchers designed a training program using cross training for two months with three training sessions per week to develop special physical traits in students. The data was collected and treated using proper statistical operations to conclude that the experimental group significantly developed all special physical traits understudy. In addition to that, the controlling group did not develop compared to the experimental group in special physical traits.